Uterine natural killer cell progenitor populations predict successful implantation in women with endometriosis‐associated infertility. (30th January 2018) - Glover, Louise E.; Crosby, David; Thiruchelvam, Uma; Harmon, Cathal; Chorcora, Cáit Ni; Wingfield, Mary B.; O'Farrelly, Cliona
Abstract : Problem: Uterine natural killer (uNK) cells play a critical role early in gestation. As we previously identified altered uNK cell development in endometriosis‐associated infertility, we herein sought to characterize natural killer (NK) cell profiles in endometriosis that may predict embryo implantation. Method of study: Study participants had a surgical diagnosis of endometriosis‐associated infertility. Endometrial tissue and peripheral blood were obtained from 58 women. Thirty‐three patients underwent artificial reproductive technology (IVF, ICSI, or IUI) within a mean of 9.5 months of surgery. NK and hematopoietic progenitor cells from endometrium and blood were analyzed by flow cytometry. Successful implantation was defined as a positive pregnancy test. Results: In successful implantation, populations of endometrial CD34 + hematopoietic stem cells were higher (3.97% vs 0.69%; P  < .0004), and coexpression of NK cell marker CD56 was increased (81.1% vs 60.9%; P  < .034) compared with patients who had failed implantation. In contrast, levels of blood NK progenitors were similar in both groups. Conclusion: Our study revealed that uterine NK progenitor cell populations are markedly different in patients with endometriosis who proceed to successful or failed embryo implantation and may define a novel predictor of implantation success. Our findings also highlight the fundamental differences inherent in NK cell repertoires between blood and uterine compartments. Abstract : Uterine natural killer cell progenitor populations predict successful implantation in women with endometriosis‐associated infertility.